KETERSEDIAAN DATA PWS-KIA UNTUK MENGHASILKAN INFORMASI KESEHATAN DALAM PROSES PENGAMBILAN KEPUTUSAN DI DINAS KESEHATAN KABUPATEN LOMBOK UTARA - , Muhamad Ainussobah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background:Data is needed to monitor and evaluate health program, including Maternal and Child Health. Availability of data ease is very needed to knowing the success level of Maternal And Child Health Program in order to able to follow up quickly and appropriately the coverage of health service that is still low. Data processing is one of main activities in Local Area Surveillance of maternal And Child Health, thus it is expected that the data and information that is that is resulted such as quick and accurate report able to be use as a base in order to support a quality decisions making in Maternal And Child Health Program. Objectives:To obtain a depiction on the data availability to produce an information on Local Area Surveillance of Maternal And Child Health that was used as a base (referrance) to support a decision making in Maternal and Child Health program. Methods:The study used qualitative approach. Observations and interview of maternal and child health program activities in Health Office of North Lombok Regency were conducted. Documentation of maternal and child health report and indicators was observed along with maternal and child health related program implementation of year 2009 to 2012. The observation focus on discrepancy of data and implemented program in each year. To strengthen the findings, a total of 20 respondent involved in the interviews to understand better the problems of program planning. Result:The pattern of decision making of maternal and child health program in District Health Office of North Lombok Regency was not based on routine collected data of maternal and child health. There were several indicators which had been decreasedbut wsa not followed by proper decision making in distrct level. It should need appropriate program activities planning for the future years in order to able to improve health performance as shown in the indicators but it was not performed, this caused the coverage number in the 13 indicators which were observed was not stable in their coverage number. Conclusions:The decision making in Maternal and Child Health Program in health office of North Lombok Regency was not based yet on data from reporting of Local Area Surveillance of Maternal and Child Health, this because the data that was obtained was not processed yet optimally.